The crown. The complete final season [videorecording (DVD)] - Morgan, Peter, 1963- (Sony Pictures Home Entertainment, 2024)
"[A] relationship blossoms between Princess Diana and Dodi Fayed before a fateful car journey has devastating consequences. Prince William tries to integrate back into life at Eton in the wake of his mother's death as the monarchy must ride the wave of public opinion. As she reaches her Golden Jubilee, the Queen reflects on the future of the monarchy with the marriage of Charles and Camilla and the beginnings of a new royal fairy tale in William and Kate" --Container.